ANALYSIS OF THE EFFECT OF USING ARTIFICIAL INTELLIGENCE (AI) AS A LEARNING RESOURCE FOR STUDENTS IN THE DIGITAL AGE - Ervil, Riko; Putri, Della Rahma; Khairi, Aziati Ridha; Idris, Idris; Abror, Abror (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
Technological developments in today’s digital era are advancing rapidly and have created significant impacts across various fields, including education—particularly in the way students access learning resources. Although AI offers convenience and efficiency, it also introduces challenges such as reduced creativity, diminished critical thinking, and increased dependence on technology. As one of the key innovations of the Industrial Revolution 4.0, AI has been widely adopted across multiple sectors, including education. This study focuses on three major AI tools: ChatGPT, Copilot, and Gemini. The purpose of this research is to identify which types of AI are most widely used and perceived as the easiest to understand as learning resources for students in the digital era, as well as to examine the influence of AI on students’ material comprehension, learning effectiveness, and academic achievement. This study employed a quantitative research method. Data were collected through an online questionnaire distributed to 400 students in West Sumatra. The data were analyzed using Simple Linear Regression and ANOVA to compare and measure the influence of each variable. The findings indicate that AI usage has a significant effect on all three variables. The study concludes that ChatGPT is the most widely used AI tool among students. ChatGPT and Gemini are also considered the easiest AI tools to understand as learning resources. Furthermore, AI usage significantly affects students’ material comprehension, learning effectiveness, and academic performance.